Structural-scaling transitions and universality of fluctuation statistics under plastic deformation of metals - Panteleev, Ivan Alexeevich; Naimark, Oleg Borisovich; Froustey, Catherine (Computational Continuum Mechanics, 2009)
The universality of statistics of plastic flow stress fluctuations in crystalline materials exhibiting self-organized criticality is studied within the conception of structural-scaling transitions in mesoscopic systems with defects. The relation between the universality of the probability density function (PDF) of stress fluctuations and the universality classes of collective modes of mesodefects is determined by finding the autosoliton (trigger)-type self-similar solutions on the spectrum of spatial structural scales of the material. It is established that the natural universality can be the dynamics of collective modes of mesodefects with pronounced long-range correlation interactions. Experimental studies of the plastic flow instability of deformed aluminum alloy, steel and Armco-iron supported the universality of the probability density function of stress fluctuations of the flow, which is similar to that of liquids within the inertial range of turbulence.